Screening Antibody Libraries with Colony Assay Using scFv-Alkaline Phosphatase Fusion Proteins - Yoshiro Hanyu; Mieko Kato (Molecules, 2020)
Screening antibody libraries is an important step in establishing recombinant monoclonal antibodies. The colony assay can identify positive clones without almost any false-positives; however, its antibody library is smaller than those used in other recombinant screening methods such as phage display. Thus, to improve the efficiency of colony assays, it is necessary to increase library size per screening. Here, we report developing a colony assay with single-chain variable fragment (scFv) fused to the N-terminus of bacterial alkaline phosphatase (scFv-PhoA). The scFv-PhoA library was constructed in an expression vector specifically designed for this study. Use of this library allowed the successful and direct detection of positive clones exhibiting PhoA activity, without the need for a secondary antibody. Colony assay screening with scFv-PhoA is simple, rapid, offers a higher success rate than previous methods based on scFv libraries, and—most importantly—it enables high-throughput procedures.